Sexual conflicts in panic disorder: a multi-case study - Munawar, Khadeeja; Bokharey, Iram Zehra; Choudhry, Riaz Fahad (Emerald Group Publishing Ltd., 2017)
Purpose – Problems related to sexual functioning have been reported in patients with anxiety disorders in general and panic disorder in particular. The past literature has shown the association of sexual conflicts of panic disorder patients with sadomasochism, and revealed the themes of: guilt, self-punishment, role of unconscious conflicts about sexuality, anger and separation. The purpose of this paper is to explore sexual conflicts in patients with panic disorder and their beliefs regarding guilt around sexual fantasies and dreams. Design/methodology/approach – Interpretative paradigm and case study method was employed. For collecting data, semi-structured interviews were recorded, transcribed and subjected to within and cross-case analyses. Clarifying researcher’s bias and rich thick description were used for verification of data. Findings – Cross-case analyses revealed themes of negative emotions, positive emotions and ambivalence. Negative emotions (i.e. guilt and anger) were experienced as threatening and harmful and caused distress to participants. Positive emotions, such as, satisfaction, pleasure and happiness were revealed in response to questions related to sexual fantasies, thoughts dreams, emotional attachment and sexual relations. Ambivalence was shown in response to questions related with reactions toward sexual fantasies, masturbatory practices, sexual relations and/or emotional attachment. Research limitations/implications – The participants of this study consisted of two self-selected individuals who had diagnosis of panic disorder with agoraphobia. The main limitation of the study is a small sample size comprising of men only. This research can provide grounds for more Asian studies in future especially by including females. Practical implications – The findings point toward addressing sexual conflict in therapeutic intervention of panic disorder. Social implications – The findings have implications in society in expanding the awareness and knowledge about sexual conflicts in clinical population and general population suffering from anxiety symptoms. Originality/value – This research study adds understanding of psychological issues in Pakistan’s socio-cultural context